The impact of COVID-19-related social restriction and containment measures on admissions for orthopedic surgery in a private hospital: cross-sectional data from a secondary healthcare provider in Turkey - Bertan Cengiz (Medicine Science, 2022)
During the COVID-19 pandemic, significant declines in the number of admissions due to several critical disorders have been reported, including cardiovascular diseases and malignancies. However, little is known regarding orthopedic admissions during the COVID-19 pandemic. This study aimed to compare the number of orthopedic surgeries prior to and during the COVID-19 pandemic in a private hospital designated as a secondary healthcare institute. The Turkish Ministry of Health announced strict containment measures and quarantining for those aged [Med-Science 2022; 11(1.000): 180-3]